Geothermal in Iceland: It's Only Natural - Gudmundsson, Jon Steinar (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1983)
If you lived in Reykjavik, the capitol of Iceland, you would heat your home with geothermal water. The city's district heating system dates back to 1930, when 15 1/s (238 gpm) of 90-100 C (194-212 F) water was piped 2.8 km (1.7 mi) to heat 70 homes, one school, and a swimming pool. The Reykjavik District Heating Service is now the largest of its kind in the world. If you were visiting Reykjavik, you would soon discover that the city is geothermally heated. The geothermal water is of good quality and is used directly for bathing and washing. Taking a bath or shower you are likely to smell the water because of the hydrogen sulphide. Reykjavik is by no means unique in having a geothermal district heating system. There are now many such systems in Iceland; they serve more than three-quarters of the total population